Estudo do bumblefoot (pododermatite) em pinguinsde- magalhães (Spheniscus magellanicus) em centro de recuperação - Osório, Luiza da Gama (2010)
Penguins are seabirds that spends about 75% of their life on the sea, and when they are found weak, this birds are sent to rehabilitation centers. Although, their extensive adaptations to sealife can become limiting issues to their life in captive, occurring, often, bumblefoot, or pododermatitis, cases: a foot disease that can evolve to septicemia and death. The Centro de Recuperação de Animais Marinhos (CRAM Marine Animals Recovery Center) is the place that, in Brazil, recieve more penguins to rahabilitation. Given the CRAM s importance in the national matter in penguin rehabilitation, the research objective was to evaluate the bumlefoot epidemiology in the birds kept captive in CRAM, trying to minimize the injuries that accompany the syndrome during rehabilitation period. Were observed 129 penguins in CRAM, where the syndrome incidence were 75%, presenting, the abrasive surface as main predisposing factor for development. The research presented the bumblefoot usually as a bilateral disease and with a progressive course. Every foot pads where qualified according the injury level to clinic evaluation, showing, by creating a method of biometric measurement of edema between each lesion score. The fungal microorganisms were related to the penguin s foot pad s transitory microbiota, being more isolated the C. albicans e Rhodotorula spp.The bacteria were related as transitory and permanent s microbiotas compounds, as well the pododermatitis epidemiology, being the more isolated genres the Staphylocossus and Corybacterium. The antibiotic that inhibited most the bacterial development against all strain tested was cefalosporina, followed by enrofloxacina, estreptomicina and penicillin. Was possible through this study highlight the syndrome s importance about penguin rehabilitation, and understand its epidemiology, enabling the implementation of precise forms of management, prophylaxis and treatment.